Analysis and Interpretation of CW Arcas Rocket Propagation Experiments Performed during the November 2, 1969 Polar Cap Absorption Event - Lee, B. W.; Seliga, T. A. (1974)
Low D region electron density profiles are deduced from the H-2, H-3, H-4, and H-6 Arcas continuous wave propagation experiments conducted at Ft. Churchill, Manitoba, Canada during the November 2, 1969 Polar Cap Absorption Event (PCA). The profiles compare favorably with others obtained during the PCA and should contribute to the total collection of data of relevant ionospheric parameters associated with the event. The results indicate a major influence of solar radiation on the ambient electron density, evident by a strong dependence of the electron density profiles on solar zenith angle. The electron density profiles are interpreted according to simple chemical models of three-body attachment processes at night, ion-ion neutralization, and possible dissociative recombination mechanisms involving water cluster and non-water cluster ions. See also AD774301.